(untitled) (Impetus, 2021)
Agility tests are often applied to classify individuals at a given level, also to recognize abilities such as coordination, speed, and strength of apparently healthy subjects. However, there is currently lack of baremación for the Colombian population, which means that there is no reliable parameter to evaluate it. For this reason, a scale is established based on an agility test applied to apparently healthy and physically active young people, students of the Santo Tomas University (Campus) and the incidence of BMI is identified. A quantitative, descriptive and transversal design study was carried out. The sample was randomly selected, informed consent, clinical history and a test denominated 10x5 were applied. The times obtained for the first measurement oscillate in a range of 17’’ 54-37’’ 57 (DS ± 2.34) and for the second measurement time ranges between 16’’ 62-30’’ 80 (DS ± 2.14). In conclusion, it is necessary to have a larger sample size and to insist on the rigor to the application and measurement of the test. The BMI is significant for the development of the test, but mainly for the component size, not for the weight. The subjects should consider the training and maintenance of agility, to denote improvements in it.